Aplikasi Jadwal Pintar Berbasis Gamifikasi untuk Optimalkan Produktivitas Waktu bagi Mahasiswa - Ade Maulana; Ferik Bagas Wardana; Muhammad Iqbal Hanafri; Neng Linda Badratul Laela (Jurnal Teknologi Informasi dan Multimedia, 2024)
Time productivity is a significant challenge for students in the digital age, where they often struggle to manage their time effectively, which can impact their academic performance and life balance. This study aims to develop and test a "Gamification-Based Smart Schedule Application" designed to enhance students' time productivity through an engaging and interactive approach. The research method employs an experimental quantitative design, encompassing needs analy-sis, design, development, and evaluation of the application with gamification elements such as leaderboards and Experience Points (XP). The application was tested with 30 students from vari-ous departments at Institut Bina Sarana Global, with data collected through pre-test and post-test questionnaires. A paired t-test was used to analyze the data and compare the mean scores of pre-test and post-test to identify significant differences in time productivity, time management, timely task completion, and student motivation. The results indicate that gamification elements positively contribute to user engagement and adherence to schedules, with significant im-provements in all measured aspects. Statistical analysis shows that the application is effective in helping students optimize their time productivity. Data analysis from the pre-test and post-test of 30 participants reveals an average score increase of 9.4 points (p < 0.05) after using the applica-tion, reflecting its effectiveness in improving time management and timely task completion. The Gamification-Based Smart Schedule Application offers an innovative solution to the time man-agement issues commonly faced by students, and the study highlights the significant potential of using gamification in educational contexts to enhance engagement and learning effectiveness.